Health promoting behaviours of the elderly in Myanmar - Aung, Khin Thandar; Win, Cho Mar; Maw, Aye Aye; Naing, Htet Htet (Scholars Academic and Scientific Publisher, 2017)
Aging is a lifelong and inevitable process. As a human being, every person wants to have a long life. With the aim to promote active and healthy ageing, the Ministry of Health implemented the elderly health care project in Myanmar since 1992-1993. This programme is based on comprehensive health care; promotion, preventive, curative and rehabilitative care. Elderly health care programme has been implemented in 161 townships by the end of year 2013 but nationwide is not yet. Nurses in Myanmar involve in the elderly health care project as a significant contribution to the health of elderly population. There is a little research that demonstrates effectiveness in quantifiable measuring health promotion practices in the elderly. There is a definite need for the elderly population to practice health promotion to improve the quality of life as their life span lengthens. This study will also encourage the nurses to better help the elderly to move to increase health promotion practices. That is why it is needed to investigate the health promoting behaviors of elderly people. This cross sectional descriptive study was done to assess health promoting behaviors of the elderly in the community. 69 elderly people aged 60 years and above including males and females who live in Chan Mya Thar Si Township, Mandalay was conducted. The Health Promoting Lifestyle Profile II (HPLP II) developed by Walker, Sechrist, and Pender (1995) was used as a research instrument and analyzed manually. The findings of this study revealed that there were 62% (n = 43) of the elderly had healthy behavior in nutrition and 38% (n = 26) of the elderly had unhealthy behavior in nutrition. Regarding physical activity, 33% (n = 23) of the elderly had healthy behavior and 67% (n = 46) had unhealthy behavior. In managing stress, the majority of participants 93% (n = 64) had healthy behavior and only 7% (n=5) were unhealthy in stress management. Concerning interpersonal relations, 59% (n = 64) were healthy and 41% (n = 28) were unhealthy. 38% (n = 25) of healthy behavior of the elderly and 64% (n = 44) of unhealthy behavior of the elderly in health responsibility, 78% (n = 54) of healthy behavior of the elderly and 22% (n = 15) of unhealthy behavior of the elderly in spiritual growth. Overall, there were 55% (n = 38) in healthy behavior and 45% (n = 31) in unhealthy behavior in this community. This quantitative study showed that the overall behavior in their community was healthier. According to this study, the areas which needed to investigate and improve in their physical activities and their taking health responsibility.